Biomedical factors associated with hospitalization of older adults: The Bambuí Health and Aging Study (BHAS) - Henrique L. Guerra; Pedro G. Vidigall; Maria Fernanda Lima-Costa
The objective of this study was to identify biomedical factors (body mass index, blood pressure, blood glucose, total cholesterol and fractions, triglycerides, and albumin) associated with hospitalization of older adults. All residents of the town of Bambuí, Minas Gerais State, ages ³ 60 years (n = 1,742) were selected for the study, of whom 1,494 (85.2%) participated. None of the biomedical factors studied was independently associated with occurrence of 1 hospitalization during the previous 12 months. Body mass index < 20Kg/m² and total cholesterol = 200-263mg/dl and ³ 264mg/dl were independently associated with ³ 2 hospitalizations. The introduction of biomedical factors did not modify the previously identified associations between hospitalization and indicators constructed from information obtained in a questionnaire survey. The results show that data easily obtained through interviews can be useful both for identifying older adults at risk of hospitalization and thus for assisting in prevention.